Tata Kelola Potensi Zakat, Infaq Dan Shodaqoh Di Desa Wisata Mojo Ngeposari Gunung Kidul - Saputra, R. Gati Reditya; Wardana, Linda Kusumastuti (Jurnal Pengabdian Dharma Bakti, 2020)
Mojo village, located in Mojo, Ngeposari, Semanu, Gunung Kidul. The distance from the city of Yogyakarta is approximately 20 km to the east. There are various types of tourism in this village, ranging from agriculture, nature tourism, cultural tourism, to handicrafts. Nature tourism is also diverse such as Goa Gesing, Goa Jlamprong, Goa Sinden, and Embung Jlamprong. However, there is one of the tourist attractions in the Mojo Tourism Village. However, it is necessary to manage governance from the potential infaq, zakat, and shodaqoh to improve the ability of the community. In terms of planning, there is no governance and transaction income that originates from the income of indigenous people because of the recording and documentation that is not optimal. The direct benefits derived from tax payments to the Government are felt to be lacking. Therefore it is necessary to conduct financial management training and management of zakat, infaq and shodaqoh management for the surrounding community so that it can be used quickly, in accordance with the budget and costs incurred during Zakat, Infaq and Shodaqoh use. By issuing good and documented zakat, infaq and shodaqoh, the manager of the Mojo hamlet will more easily get capital to develop the region's economy. The program to achieve targets and outcomes consists of two areas namely training on ZIS financial management and collection of zakat, infaq and shodaqoh for special communities in the Mojo hamlet. Each plan consists of 2 activities, namely preparation and briefing as well as implementation.Key Word: escalation of working capital, financial governance, ZIS